The Financial Flows of Terrorism and Transnational Crime - Stefan Haigner; Friedrich Schneider; Florian Wakolbinger (Deutsches Institut für Wirtschaftsforschung (DIW), 2012)
Yearly revenues from transnational criminal activity account for USD 1 to 1.6 trillion, and a wide variety of methods is employed to transfer those revenues across borders and launder it. The specific type of crime largely determines the choice of methods. Terrorists, for example, use both "legal" as well as illegal activity, in particular drug dealing, to raise funds, and largely employ the formal financial sector as well as physical cross-border transfers to move funds across borders. Money attributable to terrorism, however, accounts only for a tiny share of international proceedings from illicit activity.
info:eu-repo/grantAgreement/EC/FP7/218105
Keywords: 330